The world financial crisis and the international financing of Brazilian companies - Andre Carvalhal (BAR - Brazilian Administration Review, 2013)
The world financial crisis initiated in 2008 may have affected the international financing mix of firms in Brazil and their determinants, given its aftereffects. Financial crisis are recurrent events with varying degrees of severity. Many public Brazilian firms use international financing in their capital structure mix and it is relevant to understand their behavior during international crises. Thus, our goal was to investigate the foreign financing mixes of Brazilian listed companies before (2004) and during the 2008 world financial crisis by means of descriptive and probit regression analyses of their components and determinants at the end of these years. Brazilian companies usage of Eurobonds fluctuates with the value of the real (R$) and is still small considering the size of Brazil's economy. Short-term financing and bank loans, domestic and foreign, decreased in 2008 and were replaced by domestic and international bonds and American Depository Receipts (ADRs). Firms with foreign shareholders more often resorted to foreign capital markets and their presence became a more important determinant in 2008, while the other determinants did not change. Firms that employ international debt tend to use all other sources of financing more often. International bank loans may be the first step to reduce international financing constraints.